1968
DOI: 10.1172/jci105745
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hemorrhage and retransfusion on intrarenal distribution of blood flow in dogs

Abstract: A B S T R A C T Distribution of intrarenal blood flow was studied in 12 dogs anesthetized with Nembutal. Medullary blood flow was estimated by local clearance of hydrogen gas from the outer medulla measured polarographically with needleshaped platinum electrodes, and by local clearance of 85Kr and mean transit time of 32P-labeled erythrocytes measured with a small semiconductor detector placed in the outer medulla. Cortical blood flow was estimated from cortical red cell transit time and from total renal blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
37
0

Year Published

1968
1968
1992
1992

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 44 publications
11
37
0
Order By: Relevance
“…This hypothesis is based on the reports that hemorrhagic hypotension decreased blood flow through the superficial cortex but had little effect on blood flow through the juxtamedullary area (19,20). More recent studies, however, indicate that hemorrhagic hypotension decreases cortical and medullary blood flow to the same extent and thus do not support the concept of a selective resistance of the juxtamedullary circulation to hemorrhage (21). Conceivably, glomerular filtration rate could increase in the juxtamedullary area relative to the superficial cortical area in response to hemorrhage despite a comparable decrease in blood flow in the two areas.…”
Section: Resultsmentioning
confidence: 99%
“…This hypothesis is based on the reports that hemorrhagic hypotension decreased blood flow through the superficial cortex but had little effect on blood flow through the juxtamedullary area (19,20). More recent studies, however, indicate that hemorrhagic hypotension decreases cortical and medullary blood flow to the same extent and thus do not support the concept of a selective resistance of the juxtamedullary circulation to hemorrhage (21). Conceivably, glomerular filtration rate could increase in the juxtamedullary area relative to the superficial cortical area in response to hemorrhage despite a comparable decrease in blood flow in the two areas.…”
Section: Resultsmentioning
confidence: 99%
“…In zone 1 there was a marked decrease in the per cent of renal blood flow from 45 ±2 to 33 +2% (P < 0.001). There was no change in zone 2 whereas both FIGURE 3 Comparison of the fractional distribution of blood flow in the same area of the cortex after the injection of two different radioactive microspheres. The corresponding cortical zone for each point is given.…”
Section: Resultsmentioning
confidence: 99%
“…Aukland and Wolgast used a technique in which blood flow is measured with a hydrogen-sensitive electrode placed in different areas of the cortex (3). With this technique these authors found no alteration in the distribution of renal blood flow during hemorrhagic hypotension in sharp contrast with the results of Carriere, Thorburn, O'Morchoe, and Barger using the 'Kr technique (4).…”
Section: And Herd Havementioning
confidence: 99%
“…The cortical ischemia observed during the hypotensive period (10-13) readily explains the reduced renal blood flow since the outer medullary blood flow is relatively well maintained during hemorrhagic hypotension (11,12). This last point, however, is still subject to controversy (10,13).…”
mentioning
confidence: 99%
“…The data concerning the intrarenal distribution of the blood flow after restoration of blood pressure following hemorrhagic hypotension are sparse (12,13) and incomplete. In these studies, no definite conclusions could be established concerning the modifications of the cortical circulation because of the inconsistent results obtained in a small number of experiments.…”
mentioning
confidence: 99%